2003
DOI: 10.1001/archinte.163.12.1475
|View full text |Cite
|
Sign up to set email alerts
|

Low Lung Function and Incident Lung Cancer in the United States

Abstract: The presence of moderate or severe obstructive lung disease is a significant predictor of incident lung cancer in long-term follow-up. This finding may be useful clinically and in studies evaluating the utility of new tools for the early detection of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
110
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(118 citation statements)
references
References 27 publications
5
110
2
1
Order By: Relevance
“…This shows that compared to screening participants with normal lungs, detection rates were 4-5-fold greater in those with spirometry-based COPD or CTbased emphysema. These findings are supported by a large prospective study by MANNINO et al [7] showing over a 20 yr follow-up that lung cancer occurred 5-fold more frequently in those with spirometry-based COPD compared with normal lung function. Lastly, BECHTEL et al [8] screened exclusively current/ former smokers with COPD in a 1 yr community-based CT screening study and reported a lung cancer detection rate of 4-6%.…”
Section: To the Editorssupporting
confidence: 70%
See 1 more Smart Citation
“…This shows that compared to screening participants with normal lungs, detection rates were 4-5-fold greater in those with spirometry-based COPD or CTbased emphysema. These findings are supported by a large prospective study by MANNINO et al [7] showing over a 20 yr follow-up that lung cancer occurred 5-fold more frequently in those with spirometry-based COPD compared with normal lung function. Lastly, BECHTEL et al [8] screened exclusively current/ former smokers with COPD in a 1 yr community-based CT screening study and reported a lung cancer detection rate of 4-6%.…”
Section: To the Editorssupporting
confidence: 70%
“…However, there is growing data to suggest that a ''COPD-based'' (but not exclusive) approach to help define screening eligibility might substantially improve these rates ( fig. 1) [4,7,8]. The Pittsburgh (PA, USA) study is the only CT screening study to date that has published the results of spirometry-defined COPD and CT-based emphysema in both the screened cohort and lung cancer cases [4].…”
Section: To the Editorsmentioning
confidence: 99%
“…Within this group, 50-90% of them will have pre-existing COPD. We and others have shown previously that smokers with reduced airflow, namely FEV1 consistent with COPD (GOLD stage II or higher), carry a fourto six-fold greater risk of lung cancer compared with smokers with normal lung function [5][6][7]. We conclude that FEV1 is a very good marker for susceptibility to lung cancer [7,52].…”
Section: Discussionsupporting
confidence: 54%
“…inflammation, tissue remodelling and oxidant load. As such, they should not be considered in isolation but, rather, as two interrelated diseases [5][6][7] with overlapping genetic effects [30]. Approximately 10-15% of smokers will be diagnosed with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation